2000
DOI: 10.1111/j.1572-0241.2000.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol versus midazolam and meperidine for conscious sedation in GI endoscopy

Abstract: Propofol was associated with a statistically significant improvement in comfort and sedation score when compared to midazolam and meperidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(74 citation statements)
references
References 9 publications
3
62
0
9
Order By: Relevance
“…(10) Ancak, propofolün tek başına kullanılması halinde kolonoskopiyi yapabilmek için oldukça yüksek dozlarına (14,9 mg kg -1 sa -1 ) gereksinim duyulmaktadır. (11) Rudner ve ark.…”
Section: Discussionunclassified
“…(10) Ancak, propofolün tek başına kullanılması halinde kolonoskopiyi yapabilmek için oldukça yüksek dozlarına (14,9 mg kg -1 sa -1 ) gereksinim duyulmaktadır. (11) Rudner ve ark.…”
Section: Discussionunclassified
“…In this study, we investigated the usefulness of BIS monitoring while using propofol in the course of ESD. Propofol has been reported to afford a higher comfort and satisfaction to patients and to reduce the time to recovery, compared to previously reported drugs such as benzodiazepines and opiates [7,8] .…”
Section: Introductionmentioning
confidence: 90%
“…Thus, even after prolonged administration, it does not bring about the repeated sedation once the administration is stopped. In a controlled study of propofol versus midazolam, it has been reported that patients showed a higher level of satisfaction with propofol than with midazolam [7][8][9] . In the guidelines of endoscopy under sedation issued by the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES), it is recommended to use propofol for endoscopic treatments of long duration, due to its dual advantage of a deep sedation and a quick awakening, compared to benzodiazepines and narcotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A droga ideal para sedação durante os procedimentos endoscópicos deve possuir as seguintes caracterís-ticas: efeito imediato, sedação somente enquanto durar o procedimento, recuperação da consciência rapidamente, sem período residual de desordens mentais ou psicomotoras, e baixa incidência de efeitos colaterais. O uso rotineiro de uma droga de ação curta tem sido recomendado por muitos autores, sendo um meio para aumentar o conforto durante os procedimentos endoscópicos, resultando em procedimento de menor duração com um tempo de recuperação da consciência mais rápido 2,[4][5][6][7][8][9][10] . O propofol (2,6-diisopropylphenol) é agente aprovado pelo Food and Drug Administration (FDA) dos USA, de ação extremamente curta no sistema nervoso central, classificado como droga que promove atividade do ácido gama aminobutírico (GABA) no cérebro, com propriedades sedativas e hipnóticas.…”
unclassified
“…Causa amnésia com mínima analgesia, utilizado para induzir e manter anestesia geral e na sedação profunda em endoscopias gastrointestinais, com ventilação assistida. Circulando ligada a uma proteína plasmática, tem rápido início de ação (30 a 60 s), é metabolizada no fígado, com "clearance" hepático de 2 a 4 m, propiciando rápido recobrar da consciência e maior satisfação do paciente, em comparação com os sedativos convencionais como o midazolam e os opióides [5][6][7][8][10][11][12][13][14][15][16][17][18] . O risco do paciente ser submetido a sedação profunda, associada à depressão respiratória, deve ser considerado.…”
unclassified